Pengaruh Persepsi Kemudahan Penggunaan Dan Persepsi Kegunaan Terhadap Niat Untuk Menggunakan Dan Penggunaan Aktual Teknologi Pembayaran Digital QRIS - Erwinsyah, Erwinsyah; Ningsih, Kartina Eka; S, Syahruddin; Anjelita, Kamila (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2023)
The purpose of this study was to test and analyze the technology acceptance model which consists of the variables perceived ease of use, perceived benefits, intention to use and actual use of QRIS digital payment technology. The population in this study were students of the Faculty of Economics and Business, University of Kutai Kartanegara who used QRIS. The research sample is 60 students who use QRIS digital payment technology. Sampling used purposive sampling technique and data analysis tool used Structural Equation Modeling (SEM) using SmartPLS 4 software version 4.8.9. Based on the results of research where Perceived Ease of Use has a positive and significant effect on Intention to Use with t-statistics > t-table (2.049 > 1.96) so that the first hypothesis is accepted and proven true. Perceived usefulness has a positive and significant effect on intention to use with t-statistics > t-table (3.861 > 1.96) so that the second hypothesis is accepted and proven true. Intention to use has a positive and significant effect on actual use with t-statistics > t-table (5.514 > 1.96) so that the third hypothesis is accepted and proven true.